Ρ-Einstein Solitons on Warped Product Manifolds and Applications. (18th October 2022) - Bin Turki, Nasser; Shenawy, Sameh; EL-Sayied, H. K.; Syied, N.; Mantica, C. A.
Abstract : The purpose of this research is to investigate how a ρ -Einstein soliton structure on a warped product manifold affects its base and fiber factor manifolds. Firstly, the pertinent properties of ρ -Einstein solitons are provided. Secondly, numerous necessary and sufficient conditions of a ρ -Einstein soliton warped product manifold to make its factor ρ -Einstein soliton are examined. On a ρ -Einstein gradient soliton warped product manifold, necessary and sufficient conditions for making its factor ρ -Einstein gradient soliton are presented. ρ -Einstein solitons on warped product manifolds admitting a conformal vector field are also considered. Finally, the structure of ρ -Einstein solitons on some warped product space-times is investigated.